Malaria outbreak facilitated by engagement in activities near swamps following increased rainfall and limited preventive measures: Oyam District, Uganda. - Maureen Katusiime; Steven Ndugwa Kabwama; Gerald Rukundo; Benon Kwesiga; Lilian Bulage; Damian Rutazaana; Alex Riolexus Ario; Julie Harris (Public Library of Science (PLoS), 2022)
In April 2019, the District Health Office of Oyam District, Uganda reported an upsurge in malaria cases exceeding expected epidemic thresholds, requiring outbreak response. We investigated the scope of outbreak and identified exposures for transmission to inform control measures. A confirmed case was a positive malaria rapid diagnostic test or malaria microscopy from 1 January-30 June 2019 in a resident or visitor of Acaba Sub-county, Oyam District. We reviewed medical records at health facilities to get case-patients. We conducted entomological and environmental assessments to determine vector density, and identify aquatic Anopheles habitats, conducted a case-control study to determine exposures associated with illness. Of 9,235 case-patients (AR = 33%), females (AR = 38%) were more affected than males (AR = 20%) (p<0.001). Children <18 years were more affected (AR = 37%) than adults (p<0.001). Among 83 case-patients and 83 asymptomatic controls, 65 (78%) case-patients and 33 (40%) controls engaged in activities <500m from a swamp (ORMH = 12, 95%CI 3.6-38); 18 (22%) case-patients and four (5%) controls lived <500m from rice irrigation sites (ORMH = 8.2, 95%CI 1.8-36); and 23 (28%) case-patients and four (5%) controls had water pools <100m from household for 3-5 days after rainfall (ORMH = 7.3, 95%CI 2.2-25). Twenty three (28%) case-patients and four (5%) controls did not sleep under bed nets the previous night (ORMH = 20, 95%CI 2.7-149); 68 (82%) case-patients and 43(52%) controls did not wear long-sleeved clothes during evenings (ORMH = 9.3, 95%CI 2.8-31). Indoor resting vector density was 4.7 female mosquitoes/household/night. All Anopheles aquatic habitats had Anopheles larvae. Weekly rainfall in 2019 was heavier (6.0±7.2mm) than same period in 2018 (1.8±1.8mm) (p = 0.006). This outbreak was facilitated by Anopheles aquatic habitats near homes created by human activities, following increased rainfall compounded by inadequate use of individual preventive measures. We recommended awareness on use of insecticide-treated bed nets, protective clothing, and avoiding creation of Anopheles aquatic habitats.